Analysing Texture in Portraits. (December 2020) - Hayes, Susan
This case study is an initial exploration as to whether the depiction of texture in a set of portraits, all portraying the same Sitter, is related to the familiar likeness assessments reported in a companion paper containing a principal component analysis (PCA) of the portraits' depiction of shape. Somewhat unexpectedly, a texture PCA failed to discriminate the high from low likeness portraits, despite experimentation with different pre-processing methods to reduce the portraits' high level of uninformative, image-level texture variability. There were some findings arising from these analyses, and while only indicative at this stage, include that linear histogram matching is effective in reducing variability in portrait brightness; that depicting, and perhaps exaggerating, shading relating to lighting direction may enhance portrait likeness; and, that whether minimised or exaggerated, lighting direction can be portrayed somewhat anomalously. Furthermore, and in agreement with findings from photographs, shape and texture were not found to be independent variables, and shape-free image registration, while very usefully enabling a comparison of closely corresponding pixel coordinate values, could itself be a confounding factor for undertaking a texture PCA with portraits produced under relatively ambient conditions.